2023
DOI: 10.1002/1348-9585.12383
|View full text |Cite
|
Sign up to set email alerts
|

DigiFuehr 2.0: Novel insights for digital leadership

Abstract: Objectives Against the background of e‐government, it is discussed whether self‐organization represents an independent component of digital leadership. Addressing this research question, the instrument “DigiFuehr” is being expanded to include the aspects of self‐determination and coordination. The aim is to test the model quality of three adapted scales against the already established support‐focusing version. Methods Based on an online survey of n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Wrede et al ( 2021 ) show that within the German public administration setting (among others) older age, feeling overwhelmed, as well as resignation, are significant risk factors for digital stress. While at the beginning of the two phase study, a minority of employees across the municipalities used home office, the proportion rose to 76.4 percent during the pandemic (Claassen et al, 2022 ). In the first phase of survey results, Wrede et al ( 2021 ) found that about 10 percent of employees are digitally stressed.…”
Section: Introductionmentioning
confidence: 99%
“…Wrede et al ( 2021 ) show that within the German public administration setting (among others) older age, feeling overwhelmed, as well as resignation, are significant risk factors for digital stress. While at the beginning of the two phase study, a minority of employees across the municipalities used home office, the proportion rose to 76.4 percent during the pandemic (Claassen et al, 2022 ). In the first phase of survey results, Wrede et al ( 2021 ) found that about 10 percent of employees are digitally stressed.…”
Section: Introductionmentioning
confidence: 99%